(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2025)
The moral gap of the LGBTQIA+ community can be possibly resolved by redefining moral intuitions as a priori, a formal device devoid of content. This redefinition criticizes the classical thesis of objectivity that moral facts and moral knowledge are eternally valid for all humanity. This line of reasoning is absurd; hence, facts and information are revealed gradually and vary from period to period according to some emergency. Moreover, the claim to objectivity is problematic with the recent moral issues, like the LGBTQIA+ community. The principle is incompatible because of its established truth, where the LGBTQIA+ community is excluded. In addressing the gap, this paper proposed that: Firstly, moral intuitions such as good, right, better, ought, and their opposites should be taken as formal device, hence a priori. From these moral intuitions a moral principle can be generated where objectivity is a product of careful reflection and deliberation of rational person. This contrast with the classical thesis of objectivity that moral principles has eternal validity for all humanity. Secondly, in application, the paper argues that the LGBTQIA+ community can be a content of moral intuitions, hence of moral principle supported by the availability of facts and information of the period.